Structural equation modelling on total quality management and knowledge management for supply chain learning in Malaysian manufacturing and services industries / Dr. Loke Siew Phaik …[et al.] - Siew Phaik, Loke (Dr.); Sambasivan, Murali (Prof Dr.); G. Downe, Alan (Dr.); Ooi keng, Boon (Assoc. Prof. Dr.); Khalid, Khalizani (2011)
Supply Chain Management (SCM) competitiveness is based largely on process efficiency. To improve efficiency, Organisations depend greatly on the acquisition and utilization of knowledge about business processes, market characteristics, logistics, customer relationship management and macro-environment conditions. Synergies created via Knowledge Management (KM) efforts are powerful, particularly in the area of innovation enhancement. KM is relevant to every stage in SCM in order to make accurate and timely decisions that are critical to the firms' effectiveness and efficiency in SCM. At the same time, the Total Quality Management (TQM) concept proposes a system to improve the efficiency and productivity. Many researchers have acknowledged the importance of quality in longterm sustainability and future competitiveness (Chen, 1999; Phusavat and Kanchana, 2008). Sohal and Morrison (1995) highlighted that TQM, if practiced as a philosophy with a set of techniques, can be an effective vehicle for organisation learning. This study aims to develop and test a structural model for tracking the degree of KM and TQM effects on supply chain learning (SCL) in the manufacturing industry. It is expected that the research outputs to be useful for managers implementing KM and TQM concepts in support of their organisation's learning efforts. Due to the fast changing business environment, firms today not only need to keep pace with their customers' increased expectations in terms of cost, time, quality and choices, the research outputs would help the Malaysian manufacturing industry to respond to these challenges by leveraging the supply chain learning. Specifically, it addresses how TQM dimensions emerge with new information and knowledge in facilitating the learning process within the supply chain, and these learning activities, including knowledge sharing and knowledge creation would then become the main drivers for achieving the organisation's goals and improving the overall performance.